Unexpected contributions by carbonates and organic matter in a silicate-dominated tropical catchment: An isotope approach - Senarathne, Sachintha Lakshan; van Geldern, Robert; Chandrajith, Rohana; Barth, Johannes (Science of the Total Environment, 2024)
The understanding of global carbon has rarely extended to small-scale tropical river basins. To address these uncertainties, this study aims to investigate the importance of rock weathering and organic matter turnover in the carbon cycle in a terrain dominated by crystalline silicate rocks. The geochemical composition of the dissolved and particulate carbon phases (DIC, DOC and POC) and their stable carbon isotopes were studied in the Deduru Oya River in Sri Lanka. Dissolved inorganic carbon (DIC) was the most dominant carbon phase and its contribution to the total carbon pool varied between 67 and 89 %. Furthermore, the δ13CDIC values in the river varied between −1.1 and −16.5 ‰. The lithological characteristics and molar ratios between Ca2+, Mg2+ and HCO3− indicated rock weathering mainly by CO2 and carbonic acid. The δ13CDIC values for groundwater input were −15.9 ‰, while for carbonate weathering, mainly due to fertiliser input, they reached a value of −12.7 ‰. This input was fed into an isotope mass balance to determine the relative contributions. However, the isotope mass balance was only plausible after correcting for the effects on δ13CDIC caused by degassing and photosynthesis. Our study demonstrated that carbonate weathering and organic matter turnover are essential components of the river carbon cycle even in a silicate dominated catchment. They can represent up to 60 % of the DIC pool. Combined with the higher organic matter turnover and high pCO2 in the river water, it can be suggested that the Deduru Oya River acts as a net source of CO2 in the atmosphere. Our study shows that CO2 degassing and in-stream photosynthesis in tropical river systems need to be considered along with chemical weathering to account for carbon transport and turnover in tropical rivers.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Carbon species; CO; Deduru Oya; Isotope geochemistry; Organic matter; Rock weathering